Letter Of Credit as a Payment Instrument of the Export-Import Deal - N. A. Butakova (Теоретическая и прикладная юриспруденция)
Letter of credit — a financial term, one of the types of payment instruments between the participants of export-import contract. Today the letter of credit is recognized by financiers in all over the world as the most universal way of payment in foreign economic activity. The letter of credit allows the businessmen to solve several problems at once. The letter of credit guarantees: minimization of possible legal risks; additional insurance against unfair contractors in a foreign trade. Russian companies that have experience of working with international partners on the basis of long-term cooperation are able to reach an agreement on payment for products upon delivery. However, start-up companies have no chance to find a foreign company that would be willing to work on such conditions. In addition, payment in advance is unprofitable and not safe for the start-up traders, making the first steps in foreign markets. In this situation the letter of credit is an universal instrument of international payments.